2022
DOI: 10.3389/fcimb.2022.908997
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gut microbiome on dyslipidemia in japanese adults: Assessment of the Shika-machi super preventive health examination results for causal inference

Abstract: Dyslipidemia (DL) is one of the most common lifestyle-related diseases. There are few reports showing the causal relationship between gut microbiota (GM) and DL. In the present study, we used a linear non-Gaussian acyclic model (LiNGAM) to evaluate the causal relationship between GM and DL. A total of 79 men and 82 women aged 40 years or older living in Shika-machi, Ishikawa Prefecture, Japan were included in the analysis, and their clinical information was investigated. DNA extracted from the GM was processed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…PSC is closely related to the intestine. With the emergence of the “leaky gut” hypothesis and the “PSC microbiome” hypothesis, the gut microbiota as a potential pathogenic factor for PSC has received increasing attention [ 13 , 15 , 16 ]. In this study, we identified that the gut microbe Eubacterium rectale can act as a mediator to facilitate the occurrence and progression of PSC by mediating PC O-16:1_18:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSC is closely related to the intestine. With the emergence of the “leaky gut” hypothesis and the “PSC microbiome” hypothesis, the gut microbiota as a potential pathogenic factor for PSC has received increasing attention [ 13 , 15 , 16 ]. In this study, we identified that the gut microbe Eubacterium rectale can act as a mediator to facilitate the occurrence and progression of PSC by mediating PC O-16:1_18:1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the emergence of the “leaky gut” hypothesis and the “PSC microbiome” hypothesis, the gut microbiota has attracted increasing attention as a potential pathogenic factor for PSC [ 13 15 ]. Not only that, but changes in blood lipids have been found to be closely related to the abundance of the gut microbiota [ 16 19 ]. Consequently, the gut microbiota composition might serve as potential mediators between lipidomics and PSC.…”
Section: Introductionmentioning
confidence: 99%
“…Fecal samples were collected from 488 participants using the method described previously 29 . The stool surface samples were collected independently by the participants using clean paper (AZ-ONE, Osaka, Japan) and a clean spatula with a plastic tube (AZ-ONE, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Observational studies have identified potential relationships between gut microbiota and circulating lipids and lipoproteins, [250][251][252][253][254] with microbiota accounting for an estimated 4% to 6% of the variation in triglyceride and HDL (high-density lipoprotein) cholesterol 255 and individual microbiota associating with specific lipoprotein subclasses in obese individuals. 256 Gut microbiota may affect lipid metabolism directly through modulation of lipids within the gut and systemically, 257 with gut microbial production of SCFAs serving as the precursor for hepatic synthesis of longer chain monounsaturated fatty acids and glycerophospholipids.…”
Section: Effects Of Gut Microbiota On Lipid Metabolismmentioning
confidence: 99%